Global warming significantly increases the risk of Pierce’s disease epidemics in European vineyards - Àlex Giménez-Romero; Maialen Iturbide; Eduardo Moralejo; José M. Gutiérrez; Manuel A. Matías (Scientific Reports)
Abstract Pierce’s disease (PD) is a vector-borne disease caused by the bacteria Xylella fastidiosa, which affects grapevines in the Americas. Currently, vineyards in continental Europe, the world’s largest producer of quality wine, have not yet been affected by PD. However, climate change may alter this situation. Here we incorporate the latest regional climate change projections into a climate-driven epidemiological model to assess the risk of PD epidemics in Europe for different levels of global warming. We found a significant increase in risk above $$+\,2\,^{° }\hbox {C}$$ + 2 ∘ C in the main wine-producing regions of France, Italy and Portugal, in addition to a critical tipping point above $$+\,3\,^{° }\hbox {C}$$ + 3 ∘ C for the possible spread of PD beyond the Mediterranean. The model identifies decreasing risk trends in Spain, as well as contrasting patterns across the continent with different velocities of risk change and epidemic growth rates. Although there is some uncertainty in model projections over time, spatial patterns of risk are consistent across different climate models. Our study provides a comprehensive analysis of the future of PD at multiple spatial scales (country, Protected Designation of Origin and vineyard), revealing where, why and when PD could become a new threat to the European wine industry.